235k views
5 votes
X + 4y = 23
-2x + 3y = -2

User Guyfromfl
by
7.6k points

1 Answer

3 votes

Answer:

(x, y) = (7, 4)

Explanation:

I find a graphing calculator to give a solution quickly and easily.

(x, y) = (7, 4)

__

Here, we can solve the first equation for x, then substitute into the second.

x = 23 -4y

-2(23 -4y) +3y = -2 . . . . . substitute for x

-46 +8y +3y = -2 . . . . . eliminate parentheses

11y = 44 . . . . . . . . . . . collect terms

y = 4 . . . . . . . . . . . . divide by the coefficient of y

x = 23 -4·4 = 7 . . . . use the expression for x to find x

(x, y) = (7, 4)

X + 4y = 23 -2x + 3y = -2-example-1
User Sesh
by
7.3k points